Mental Health Symptomatology and Posttraumatic Growth among Those with Multimorbidity in COVID Pandemic: Cross-Sectional Findings from the STRONG Study in Greece - Katerina Kavalidou; Konstantinos Kotsis; Dimitra Laimou; Dionysia Panagidou; Olga Megalakaki (Psychiatry International, 2021)
Background: Individuals with physical or mental health conditions represent a vulnerable population, especially during the COVID-19 pandemic. However, limited information is available concerning posttraumatic growth and common mental health symptoms of this vulnerable health group during COVID-19. Methods: An online cross-sectional study (STRONG study; psychological changes and effects after COVID-19 quarantine in Greece) was conducted from 28 September 2020 (no lockdown restrictions) to 2 November 2020, just before the second lockdown in Greece. Main outcomes were depressive and anxiety symptoms as well as posttraumatic growth. Results: A total of 860 adults participated in the study. A high proportion of participants did not report any pre-existing health condition (61%), while 334 individuals reported one or more physical or mental health conditions. Overall, 20.2% of the participants reported significant depressive symptoms, and 27.9% reported moderate to high posttraumatic growth. The presence of physical and mental health conditions, either as single diagnosis or as a multimorbidity, was significantly associated with the development of depressive symptomatology (either physical or mental health conditions: OR = 1.12; 95% CI, 1.07–1.17, p < 0.001; both physical and mental health conditions: OR = 1.23; 95% CI, 1.14–1.33, p < 0.001). Posttraumatic growth did not differ between those with or without any pre-existing health issue. Conclusions: Although having a physical or/and a mental health condition predicted the development of depressive symptomatology in a post-lockdown period, the presence of pre-existing conditions was not associated with posttraumatic growth development. Clinicians should be aware of depressive symptoms among their multimorbid patients, even after exiting lockdown.